Optimising Investments in the Tuberculosis Response of Gauteng Province, South Africa : Findings from a Pilot Application of the Optima TB Model - World Bank (World Bank, Washington, DC, 2020)
South Africa remains a high-burden country for tuberculosis (TB) and multi-drug resistant TB (MDR-TB) with an underlying generalised HIV epidemic. TB funding must therefore be allocated to interventions which provide high impact to prevent TB transmission, identify TB cases and treat them successfully. This report presents the findings from a pilot application of the Optima TB model in Gauteng Province, where many challenges remain to sustainably reduce TB. The modelling analysis focused on relevant intervention scenarios and optimal resource allocation to achieve the 2022 TB targets, using the mathematical optimisation feature of the tool. Findings suggest that further reductions in TB prevalence and deaths are possible through improved allocative efficiency. Several scenarios highlight opportunities especially in HIV negative populations by improving the TB care cascade with higher diagnosis rates, enhanced linkage to treatment and better MDR treatment outcomes using shorter drug regimens. The same budget allocated differently could, by 2022, reduce active TB infections by up to 40 and reduce TB deaths by up to 30 perent among HIV positive and HIV negative populations. The study provided valuable input into the refinement of the Optima TB model, especially for the HIV/TB co-epidemic setting. The model outputs support Gauteng's focus on improving the care cascade and innovating MDR-TB treatment.